Enhancing Customer Engagement Through Social Media Content Strategy in Architecture Industry - Sapta, Muhammad (Universitas Muhammadiyah Pontianak, 2025)
This study investigates how social media content strategy can enhance customer engagement and influence purchase intention and electronic word-of-mouth (eWOM) in the architecture and interior design industry in Indonesia. Drawing on the Uses and Gratifications (U&G) theory and the Theory of Reasoned Action (TRA), the research examines how different content strategies (educational, inspirational, entertainment, and trust-building) and content characteristics (vividness, interactivity, immersiveness, and informativeness) affect customer engagement, which in turn mediates their impact on marketing outcomes. Using a quantitative approach, data were collected from 220 respondents familiar with design studios’ Instagram accounts. The results, analyzed through Partial Least Squares Structural Equation Modeling (PLS-SEM), indicate that content characteristics particularly interactivity and immersiveness have a significant positive effect on customer engagement. In contrast, content strategy dimensions show no significant direct effect. Customer engagement strongly predicts both purchase intention and eWOM, and also serves as a partial mediator in the model. These findings highlight the importance of designing immersive and interactive content to foster engagement in social media marketing for design studios. The study offers a practical implementation roadmap, encouraging small studios to prioritize digital strategies that emphasize audience interaction and experience rather than static information-sharing.